Clio’s (mis)adventures with Hermes, Hestia, and Hephaestus - Ferla, Luís; Laguardia, Rafael; Lesser , Jeffrey; Britt , Andrew G.; Rogers , Thomas D.; Atique , Fernando; Donato Fook, Karla; Vijaykumar , Nandamudi; Leal Musa , Daniela; Rebelo , Luciana; Torres , Aracele; Alves Barbour, Ana Maria; et al. (Historiografías, 2023)
This article shall reflect on how emerging technologies and the so-called “spatial turn” impact the historian’s craft. Looking at the past, the authors identify historical antecedents of both tendencies in the second generation of the Annales School. Eyeing the present and the future, the authors advance the concept of “border space” as an analytical tool to illuminate characteristics and trends in the digitized production of knowledge about the past. The article argues that some of the key values that characterize this border space – open-source scholarship, horizontal collaboration, and the free circulation of knowledge – can stimulate more democratic methods of producing historical scholarship.KeywordsDigital humanities, digital history, Annales School, historiographical culture